Plasmonic optical fiber gratings based on few-layer Ta2C MXenes for refractive index sensing. (26th February 2023) - Liu, Runcheng; Yang, Wen; Lu, Jiajun; Shafi, Muhammad; Jiang, Mingshun; Jiang, Shouzhen
Abstract: Tilted fiber Bragg grating (TFBG) is a widespread approach for developing refractive index (RI) sensors. The unique optoelectronic properties exhibited by MXene are expected to enhance the performance of TFBG-SPR sensors. In this study, a Ta2 C coating appropriate for sensing was obtained by optimizing the photo-deposition time, which addressed the challenge of preparing large areas of MXene. The uniform coating of the few-layer Ta2 C increases the wavelength sensitivity and FOM of the sensor to 229.5 nm/RIU and 2228.15 respectively. This significant enhancement was attributed to an ordered MXene phase of the grown Ta2 C. The energy band theory verified the metallic nature of the Ta2 C and the amplification effect on the RI response. Finite element analysis demonstrated that the stronger absorption band of Ta2 C facilitated the generation of surface plasmon polariton. Based on the above benefits, the sensor detected melamine in milk with a detection limit of 7.9 × 10 −9 M. The TFBG/Au/Ta2 C sensor is a promising approach for biochemical analysis and trace detection.